2013
DOI: 10.1097/cad.0b013e3283618b7b
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of the combination of temsirolimus and pazopanib in advanced solid tumors

Abstract: Objectives Inhibition of either vascular endothelial growth factor receptor (VEGFR) or mammalian target of rapamycin (mTOR) signaling improves outcomes in patients with several advanced solid tumors. We conducted a phase I trial of temsirolimus with pazopanib to investigate the feasibility of simultaneous “vertical inhibition” of VEGFR and mTOR pathways. Methods Patients with advanced solid tumors, no prior pazopanib or mTOR inhibitor, good performance status and acceptable end-organ function were eligible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“… a The five studies where no safe dose was found or study was aborted early due to unacceptable toxicity were excluded from this table and include: bevacizumab and sorafenib [ 28 , 29 ], pazopanib and temsirolimus [ 27 ], bevacizumab and everolimus [ 31 ], and bevacizumab and temsirolimus [ 32 ] b First drug had the dose percentage closest to the FDA-approved/RP2D/MTD dose c In these cases, the combinations were same class (small molecule inhibitors) with non-overlapping targets (sorafenib at 100% with everolimus at 25%, and imatinib at 100% with everolimus at 25%) [ 12 14 ]. d Sunitinib was at 75% and everolimus at 29% [ 20 ] e Rapamycin was at 93% and bevacizumab was at 50% [ 19 ] f Bevacizumab with vatalinib [ 26 ] and bevacizumab with telatinib [ 25 ] each included an anti-VEGF antibody and a small molecule VEGFR inhibitor (both at 10% and 50%, respectively) g Sorafenib was at 50% and temsirolimus at 40% [ 23 ]; however the combination of pazopanib and temsirolimus was above the FDA-approved/RP2D/MTD at an additive dose percentage of 65% (albeit with no acute or irreversible side effects and with the nonspecific side effect of fatigue as dose limiting in one patient).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a The five studies where no safe dose was found or study was aborted early due to unacceptable toxicity were excluded from this table and include: bevacizumab and sorafenib [ 28 , 29 ], pazopanib and temsirolimus [ 27 ], bevacizumab and everolimus [ 31 ], and bevacizumab and temsirolimus [ 32 ] b First drug had the dose percentage closest to the FDA-approved/RP2D/MTD dose c In these cases, the combinations were same class (small molecule inhibitors) with non-overlapping targets (sorafenib at 100% with everolimus at 25%, and imatinib at 100% with everolimus at 25%) [ 12 14 ]. d Sunitinib was at 75% and everolimus at 29% [ 20 ] e Rapamycin was at 93% and bevacizumab was at 50% [ 19 ] f Bevacizumab with vatalinib [ 26 ] and bevacizumab with telatinib [ 25 ] each included an anti-VEGF antibody and a small molecule VEGFR inhibitor (both at 10% and 50%, respectively) g Sorafenib was at 50% and temsirolimus at 40% [ 23 ]; however the combination of pazopanib and temsirolimus was above the FDA-approved/RP2D/MTD at an additive dose percentage of 65% (albeit with no acute or irreversible side effects and with the nonspecific side effect of fatigue as dose limiting in one patient).…”
Section: Resultsmentioning
confidence: 99%
“… a The five studies where no safe dose was found or study was aborted early due to unacceptable toxicity were excluded from this table and include: bevacizumab and sorafenib [ 28 , 29 ], pazopanib and temsirolimus [ 27 ], bevacizumab and everolimus [ 31 ], and bevacizumab and temsirolimus [ 32 ] …”
Section: Resultsmentioning
confidence: 99%
“…Temsirolimus has also been combined with oral tyrosine kinase inhibitors with anti-angiogenic effects. The combinations of temsirolimus with pazopanib were intolerable due to significant fatigue, leukopenia and electrolyte disturbances [ 26 ]. In the phase 1 study of temsirolimus with sunitinib, DLTs observed included rash, thrombocytopenia, stomatitis, diarrhea and stomatitis, and the combination was also found to be intolerable [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This combination was shown to be tolerable and had modest clinical activity however recent phase I trials combining mTOR inhibitors with anti-angiogenic TKIs have shown conflicting results. A phase I study of the combination of temsirolimus and pazopanib (a pan-VEGF receptor inhibitor) in advanced solid tumours including CRC showed high levels of grade 3 and higher toxicities as doses far less than the approved dose of each drug as a single agent [128] . Overlapping mTOR inhibitor and VEGFR TKI toxicities could account for the unfeasibility of this combination and further research is required to understand these potential interactions and evaluate alternate treatment strategies to circumvent these toxicities.…”
Section: Targetting the Mtor Pathway In Clinical Trialsmentioning
confidence: 99%